Ecofriendly remediation of cadmium, lead, and zinc using dead cells of Microcystis aeruginosa - Mohamad S. Abdelkarim; Mohamed H. H. Ali; Doaa A. Kassem (Scientific Reports)
Abstract The utilization of cyanobacteria toxin-producing blooms for metal ions adsorption has garnered significant attention over the last decade. This study investigates the efficacy of dead cells from Microcystis aeruginosa blooms, collected from agricultural drainage water reservoir, in removing of cadmium, lead, and zinc ions from aqueous solutions, and simultaneously addressing the mitigation of toxin-producing M. aeruginosa bloom. Some physical characterization of the dead biomass was performed, including scanning electron microscope (SEM) which revealed that, the cells form a dense, amorphous cluster, energy-dispersive X-ray (EDX) spectroscopy confirmed that carbon, oxygen, and nitrogen are the predominant elements in the biomass, Fourier transformation infrared (FTIR) spectroscopy identified several active function groups, including hydroxyl, aliphatic C–H amide I and amide II bands, carboxylate and carbonyl (C=O). Key factors influencing the adsorption process were examined. Under optimal conditions—pH 6, a biosorbent dose of 0.3 g, contact time of 90 min, primary metal level of 100 mg/L and temperature of 35 °C (313K)—a maximum removal efficiency exceeding 90% was achieved. Isothermal analysis revealed that the adsorption of Cd(II), Pb(II), and Zn(II) followed the Langmuir isotherm model (R2 = 0.96, q max > 67 mg/g). Kinetic studies indicated that the pseudo-second-order model best described the adsorption process (R2 > 0.94 and q e  > 81.3 mg/g.), suggesting a dominant chemisorption mechanism. Thermodynamic analysis indicated that the adsorption process is spontaneous and endothermic. The findings highlight the potential of M. aeruginosa dead cells as a low-cost, sustainable biosorbent for the removal of heavy metal in wastewater treatment applications.